2011
DOI: 10.1007/s00134-011-2179-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged weaning and survival during ventilator weaning in a respiratory ICU

Abstract: Because of the similar characteristics and outcomes, the differentiation between simple and difficult weaning had no relevant clinical consequences in a respiratory ICU. Patients with prolonged weaning had the worst outcomes. For the overall population, hypercapnia at the end of spontaneous breathing predicts prolonged weaning and a worse survival, and clinicians should implement measures aimed at improving weaning outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 36 publications
5
96
1
6
Order By: Relevance
“…The results of the Spanish study [3] largely confirm the Austrian findings [2]. First, clinical characteristics and outcome of patients with simple and difficult weaning were similar.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…The results of the Spanish study [3] largely confirm the Austrian findings [2]. First, clinical characteristics and outcome of patients with simple and difficult weaning were similar.…”
supporting
confidence: 78%
“…Second, as reported in the past [4][5][6], prolonged weaning was associated with more complications and greater mortality. Finally, in both studies [2,3] the total duration of mechanical ventilation and the duration of ICU stay were longer with prolonged weaning than with simple weaning. The latter finding is not surprising considering how the weaning categories were defined.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…A previous study demonstrated that patients with long periods of mechanical ventilation had high rates of respiratory failure after extubation. 31 Thus, to prevent re-intubation, it was not adequate for caregivers to pay attention only to the weak cough peak flow subjects. Furthermore, the reason the two cough peak flow measurements showed different predictive accuracy in cooperative subjects is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 Although some of this association may be explained by the fact that patients who require re-intubation are more likely to have comorbid conditions that independently increase the risk of mortality, most studies that adjust for severity of illness and incidence of comorbidities show an independent association between extubation failure and mortality. 9,11 This may be explained partly by the adverse outcomes associated with prolonged mechanical ventilation; however, a recent study by Thille et al 10 suggests that failed extubation or unplanned extubation is directly linked to a clinical deterioration that might explain the increase in mortality. Evidence suggests that re-intubation due to liberation failure is associated with worse outcomes and higher mortality than re-intubation due to extubation failure.…”
Section: Extubation Failurementioning
confidence: 99%